Bisphenol A Does Not Mimic Estrogen in the Promotion of the In Vitro Response of Murine Dendritic Cells to Toll-Like Receptor Ligands - Marita Chakhtoura; Uma Sriram; Michelle Heayn; Joshua Wonsidler; Christopher Doyle; Joudy-Ann Dinnall; Stefania Gallucci; Rebecca A. Roberts (Hindawi Limited, 2017)
Sex hormones affect immune responses and might promote autoimmunity. Endocrine disrupting chemicals such as bisphenol A (BPA) may mimic their immune effects. Conventional dendritic cells (cDCs) are pivotal initiators of immune responses upon activation by danger signals coming from pathogens or distressed tissues through triggering of the Toll-like receptors (TLRs). We generated in vitro murine cDCs in the absence of estrogens and measured the effects of exogenously added estrogen or BPA on their differentiation and activation by the TLR ligands LPS and CpG. Estrogen enhanced the differentiation of GM-CSF-dependent cDCs from bone marrow precursors in vitro, and the selective estrogen receptor modulators (SERMs) tamoxifen and fulvestrant blocked these effects. Moreover, estrogen augmented the upregulation of costimulatory molecules and proinflammatory cytokines (IL-12p70 and TNFα) upon stimulation by TLR9 ligand CpG, while the response to LPS was less estrogen-dependent. These effects are partially explained by an estrogen-dependent regulation of TLR9 expression. BPA did not promote cDC differentiation nor activation upon TLR stimulation. Our results suggest that estrogen promotes immune responses by increasing DC activation, with a preferential effect on TLR9 over TLR4 stimulation, and highlight the influence of estrogens in DC cultures, while BPA does not mimic estrogen in the DC functions that we tested.